Utilization of Proso Millet with or without Enzyme Supplementation on the Performance of Broiler Chicken - Verma, Urwashi; Barmase, B.S.; Wade, M.R. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to evaluate the effect of enzyme supplementation on utilization of proso millet on the performance of broilers chicken. Five hundred, day-old commercial broiler chicks were distributed into five treatments having four replicates containing 25 chicks in each, reared on deep litter system in pens up to 6 weeks of age. The dietary treatments were formulated incorporating raw or crushed proso millet replacing 50% maize. Thus, the dietary treatments were: control without proso millet and enzyme (T0), intact proso millet without enzyme (T1), intact proso millet with enzyme Natugrain TS @ 125 g/MT (T2), crushed proso millet without enzyme (T3) and crushed proso millet with enzyme Natugrain TS @ 100 g/MT (T4). The enzyme supplemented groups had higher (P<0.01) body weights than the control group. Feed intake and feed conversion ratio and dressing percentage were similar in all the treatments, however, crushed proso millet with enzyme reduced the feed cost.